Decomposition of Disaster Region using Earthquake Parameter and STDM Distance: Catastrophe Bond Pricing Single Period - Wulan Anggraeni; Sudradjat Supian; Sukono; Nurfadhlina Abdul Halim (Semarak Ilmu Publishing, 2024)
Indexed by MyCite